Local control of perivascular malignant liver lesions using percutaneous irreversible electroporation: initial experiences - Eller, Achim; Schmid, Andrea; Schmidt, Joachim; May, Matthias; Brand, Michael; Saake, Marc; Uder, Michael; Lell, Michael (Cardiovascular and Interventional Radiology, 2015)
This study was designed to assess efficacy and safety in the treatment of perivascular malignant liver lesions using percutaneous, computed tomography (CT)-guided irreversible electroporation (IRE).Fourteen patients (mean age 58 ± 11 years) with 18 malignant liver lesions were consecutively enrolled in this study. IRE was performed in patients not eligible for surgery and lesions abutting large vessels or bile ducts. Follow-up exams were performed using multislice-CT (MS-CT) or MRI.Medium lesion diameter was 20 ± 5 mm. Ten of 14 (71 %) were successfully treated with no local recurrence to date (mean follow-up 388 ± 160 days). One case left initial tumor control unclear and additional RFA was performed 4 weeks after IRE. Complications occurred in 4 of 14 (29 %) cases. In one case, intervention was terminated and abdominal bleeding required laparotomy. In two cases, a postinterventional hematothorax required intervention. In another case, abdominal bleeding could be managed conservatively. No complications related to the bile ducts occurred.Percutaneous IRE seems to be effective in perivascular lesions but is associated with a higher complication rate compared with thermoablative techniques.
EVALuna2:14379